2014
DOI: 10.1007/s00253-014-5956-4
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli W shows fast, highly oxidative sucrose metabolism and low acetate formation

Abstract: Sugarcane is the most efficient large-scale crop capable of supplying sufficient carbon substrate, in the form of sucrose, needed during fermentative feedstock production. However, sucrose metabolism in Escherichia coli is not well understood because the two most common strains, E. coli K-12 and B, do not grow on sucrose. Here, using a sucrose utilizing strain, E. coli W, we undertake an in-depth comparison of sucrose and glucose metabolism including growth kinetics, metabolite profiling, microarray-based tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 64 publications
3
25
0
Order By: Relevance
“…The glucose uptake rates measured for the different strains were observed to vary more than 3-fold in anaerobic conditions. If the measured wild-type uptake rates can be even partially conserved when generating a bioprocessing strain, selection on this criterion alone could have major implications for strain productivity and bioprocess titres (Arifin et al, 2014). Also, there are a number of cases where some strains have additional or are lacking certain metabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glucose uptake rates measured for the different strains were observed to vary more than 3-fold in anaerobic conditions. If the measured wild-type uptake rates can be even partially conserved when generating a bioprocessing strain, selection on this criterion alone could have major implications for strain productivity and bioprocess titres (Arifin et al, 2014). Also, there are a number of cases where some strains have additional or are lacking certain metabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of both closely related strains (K-12 strains) and more distantly related strains also allowed an examination of whether close genetic relatedness is a useful predictor of physiological relatedness and production potential. The existing body of work evaluating different E. coli strains in metabolic engineering and synthetic biology (Archer et al, 2011, Arifin et al, 2014, Yoon et al, 2012, Vijayendran et al, 2007, Marisch et al, 2013, Chae et al, 2010) demonstrated a need for the comprehensive analysis of strain-specific differences. Despite significant success in engineering E. coli for industrial production of chemicals and proteins (Lee et al, 2012b, Kim et al, 2015), there is no unified fundamental basis for selection of one strain over another for a given metabolic engineering project or expression of a given construct.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli are often used as a model prokaryote for genomic and physiological studies (Archer et al, 2011;Arifin et al, 2014;Ishii et al, 2007;Vijayendran et al, 2007;Yoon et al, 2012), and as host strains for industrial bioprocesses (Chae et al, 2017;S. S.Y.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism was the first example of phosphorylation control reported in a prokaryote [67]. Here we show that the glyoxylate shunt is in addition to other mechanisms of control [68], controlled by a cascade mechanism of posttranslational modification [69] where, in addition to Icd, the ratio of phosphorylation for enzymes Mdh, Pck and AcnB change when cells are grown on acetate. Our data suggests that unphosphorylation of Mdh, Pck and AcnB plays a key role in activating and controlling the glyoxylate shunt.…”
mentioning
confidence: 58%
“…This was recently shown in E. coli by integrating fluxes into absolute quantification of protein and transcripts [69]. By determining the regulation levels of metabolic fluxes for E.coli to achieve faster growth, it was found that post transcriptional modifications is the key mechanism of control of the E. coli central metabolism.…”
Section: Accepted M Manuscriptmentioning
confidence: 96%